2013
DOI: 10.1111/all.12255
|View full text |Cite
|
Sign up to set email alerts
|

Nasal hyper-reactivity is a common feature in both allergic and nonallergic rhinitis

Abstract: We found no quantitative or qualitative differences in nasal hyper-reactivity between AR and NAR patients. It is not possible to differentiate NAR subpopulations based on physical or chemical stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 35 publications
(43 reference statements)
3
61
1
7
Order By: Relevance
“…Interestingly though, a higher proportion of children in the LAR (85.7%) group reported symptoms to at least one non‐specific NHR trigger as opposed to the AR (71.4%) and non‐LAR NAR (47.1%) group without this being statistically significant. It has been already reported that NHR cannot discriminate between NAR and AR, and our results extend this observation in LAR. These results indicate that it may be difficult for a clinician to distinguish the LAR children based on the clinical history alone.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, a higher proportion of children in the LAR (85.7%) group reported symptoms to at least one non‐specific NHR trigger as opposed to the AR (71.4%) and non‐LAR NAR (47.1%) group without this being statistically significant. It has been already reported that NHR cannot discriminate between NAR and AR, and our results extend this observation in LAR. These results indicate that it may be difficult for a clinician to distinguish the LAR children based on the clinical history alone.…”
Section: Discussionmentioning
confidence: 99%
“…During exposure, there was an increase in blood flow specifically to the odour-sensitive brain regions, suggesting that a neurological response is critically involved in the pathogenesis of NAR [122]. Furthermore, recent results demonstrated that nasal hyper-reactivity is as common in NAR as in AR, but importantly, no inflammatory cells or mediators are present [123]. These data emphasize the non-inflammatory nature of this condition and suggest that in a subgroup of patients with non-allergic rhinitis, neuronal functional abnormalities may be responsible for their symptoms.…”
Section: Non-allergic Rhinitis Without Eosinophiliamentioning
confidence: 99%
“…It can be used to study nasal valve collapse , hormonal influences on the nasal mucosa and for the evaluation of nasal surgery outcome , and it has been recommended by many authors as a valuable objective instrument for evaluation of subjective nasal obstruction . PNIF can also be used in nasal provocation testing to evaluate nasal hyper‐reactivity and to evaluate environmental effects on nasal patency in occupationally induced nasal obstruction .…”
Section: Objective Measurements Of Nasal Airflow and Patencymentioning
confidence: 99%